Penggunaan E-book Antic (Tolerant and Sympathetic) sebagai Media Pembelajaran PAI untuk Membentuk Akhlak Terpuji Siswa Sekolah Dasar - Muhammad Azrul Hakim; Mutiara Chantikania; Nurul Lubna Gajalba; Siska Agustina; Ani Nur Aeni (Journal on Education, 2023)
The development of digital technology can provide various innovations in the world of education. It's the same with E-books which exist as ICT-based learning media. However, technology can also be something to watch out for, moreover, many children, especially elementary school students, already use gadgets in their daily lives. Due to various considerations, the researcher decided to make an innovation in the form of the Antic E-book (Tolerant and Sympathetic) which contains learning about tolerance and sympathy which aims to form commendable morals, both in real life and in cyberspace (social media). Seeing from this, the researcher conducted research using the Design and Development (D&D) model with the research subjects namely class VI students at SDN Sindang II with a total of 28 students. Based on the results of field research, only 90% of students in grade VI have a high level of enthusiasm for learning, besides that learning motivation and enthusiasm for using e-books only affect 90% of the total number of students. As for students' understanding of using the E-book during learning, only 85% of students from the total number of students is evidenced by questions that can be answered according to the context of the material presented.